Amide Proton Transfer Weighted Imaging Shows Differences in Multiple Sclerosis Lesions and White Matter Hyperintensities of Presumed Vascular Origin - Sartoretti, Elisabeth; Sartoretti, Thomas; Wyss, Michael; Becker, Anton S.; Schwenk, Árpád; van Smoorenburg, Luuk; Najafi, Arash; Binkert, Christoph; Thoeny, Harriet C.; Zhou, Jinyuan; Jiang, Shanshan; Graf, Nicole; et al. (Frontiers in Neurology, 2019)
Objectives To assess the ability of amide proton transfer weighted (APTw) imaging to discriminate between multiple sclerosis lesions (MSL) and white matter hyperintensities of presumed vascular origin (WMH) and to compare APTw signal intensity of healthy white matter (healthy WM) with APTw signal intensity of MSL and WHM. Materials and Methods A total of 27 patients (16 female, 11 males, mean age 39.6 years) with multiple sclerosis, 35 patients (17 females, 18 males, mean age 66.6 years) with small vessel disease (SVD) and 20 healthy young volunteers (9 females, 11 males, mean age 29 years) were included in the MSL, the WMH and the healthy WM group. MSL and WMH were segmented on fluid attenuated inversion recovery (FLAIR) images underlaid onto APTw images. Histogram parameters (mean, median, 10th, 25th, 75th, 90th percentile) were calculated. Mean APTw signal intensity values in healthy WM were defined by "Region of interest" (ROI) measurements. Wilcoxon rank sum tests and receiver operating characteristics (ROC) curve analyses of clustered data were applied. Results All histogram parameters except the 75th and 90th percentile were significantly different between MSL and WMH (p=0.018 - p=0.034). MSL presented with higher median values in all parameters. The histogram parameters offered only low diagnostic performance in discriminating between MSL and WMH. The 10th percentile yielded the highest diagnostic performance with an AUC of 0.6245 (95% CI: [0.532, 0.717]). Mean APTw signal intensity values of MSL were significantly higher than mean values of healthy WM (p=0.005). The mean values of WMH did not differ significantly from the values of healthy WM (p=0.345). Conclusions We found significant differences in APTw signal intensity between MSL and WMH and between MSL and healthy WM. Low AUC values from ROC analyses, however, suggest that it may be challenging to determine type of lesion with APTw imaging.